Implementasi Scatter Plot Dan Fault Tree Analysis Sebagai Upaya Meningkatkan Keunggulan Daya Saing Berkelanjutan (Studi Kasus Di Pt. X Pada Cacat Jahitan Rusak) - Kurniaji, Kalfajrin; Suriansha, Reza (Cv. Syntax Corporation Indonesia, 2025)
The garment industry is a strategic sector that contributes significantly to the national economy, but still faces challenges especially in quality. This study aims to identify the causes of broken stitch at PT. X and formulate improvement to increase sustainable competitive advantage. The method used is Scatter Plot to analyze the relationship between production and broken stitches, and Fault Tree Analysis (FTA) to find the root cause of the problem. The results of the Scatter Plot analysis indicate a fairly strong positive linear relationship between production volume and the number of broken stitches, with an average defect proportion of 0.423% throughout 2023. Meanwhile, FTA identified five main factors causing defects: materials, machines, people, methods, and the environment. The dominant factors coming from the quality of raw materials, inadequate machine maintenance, operator negligence, and irrelevant SOPs. Based on these findings, improvement efforts are focused on strengthening material quality standards, regular machine maintenance, operator training, and optimizing the work environment. This study concludes that the application of Scatter Plot and FTA can reduce the level of broken stitches, improve product quality, reduce rework costs that prevent penalty payments that could potentially harm the company, which leads to increased sustainable competitive advantage.